Ecos do interior da região sul: mais de 70 anos de dedicação à música com o educador Anildo Diettrich - Diettrich, Alessandra (2019)
This dissertation, linked to the Education and Arts - LP4 research line of the Post-Graduation Program in Education, and to the NarraMus research group from the Federal University of Santa Maria, aims to investigate to what extent an educator like Anildo Diettrich, without an academic background, has developed a music teaching-learning process, which has been going on for more than 70 years. In addition, we seek to identify which methodological strategies and musical practices used by the regent in his non-formal educational activities, developed with students from different ages and social classes. At the same time, we are also concern his training trajectory and the implications of his work in the contexts in which he acted. From a qualitative approach, this research has as theoretical basis, researches and studies that refer to Life History, narratives, memories and experience. For the data production, interviews, conversations, documental and photographic records were carried out in order to understand the proposed objectives. The methodology adopted by Anildo Diettrich his educational activities are intertwined with his own way of living. Ethical principles, religious and family values, associated with the methodologies of the first phase of musical educators, are mixed by Anildo Diettrich with the objective of builing his musial background, beause, his conception is that music is possible for all. And in this thought, Anildo adapts ways to build knowledge, without losing sight of the traits of Hausmusik (music at home) present in his pedagogy. One can perceive, through Anildo's musical practice, that none methodology is finite or superior to another, and there is the possibility of completing and modifying themselves when in harmony with the abilities and the possibilities of students to overcome their own limits. Anildo Diettrich has lived for a while in a society that had, especially in choirs, bands, musical and artistic groups, a way of expanding relationships, thus facilitating a great cultural and social bond with the family and his ways of life. While in the past of Anildo, music was a habit, somewhat formative, today it is treated just as entertainment. The participation in music was amateur, the main concern was with the collective and the social. Today, musicians become professionals and the study of music has become increasingly individualized. The influences of Anildo Diettrich as an educator reflect on my pedagogical practice, some similar, and others totally different, making me think and think over, building new meanings and learning.